Iron oxide nanoflowers encapsulated in thermosensitive fluorescent liposomes for hyperthermia treatment of lung adenocarcinoma - Maria Theodosiou; Elias Sakellis; Nikos Boukos; Vladan Kusigerski; Beata Kalska-Szostko; Eleni Efthimiadou (Scientific Reports, 2022)
Abstract Magnetic hyperthermia (MHT) is in the spotlight of nanomedical research for the treatment of cancer employing magnetic iron oxide nanoparticles and their intrinsic capability for heat dissipation under an alternating magnetic field (AMF). Herein we focus on the synthesis of iron oxide nanoflowers (Nfs) of different sizes (15 and 35 nm) and coatings (bare, citrate, and Rhodamine B) while comparing their physicochemical and magnetothermal properties. We encapsulated colloidally stable citrate coated Nfs, of both sizes, in thermosensitive liposomes via extrusion, and RhB was loaded in the lipid bilayer. All formulations proved hemocompatible and cytocompatible. We found that 35 nm Nfs, at lower concentrations than 15 nm Nfs, served better as nanoheaters for magnetic hyperthermia applications. In vitro, magnetic hyperthermia results showed promising therapeutic and imaging potential for RhB loaded magnetoliposomes containing 35 nm Nfs against LLC and CULA cell lines of lung adenocarcinoma.